Immature papaya juice to treat gastric ulcer in students of the Universidad Privada de Huancayo. - Junchaya Yllescas, Vilma Amparo (2020)
In Peru, gastric ulcer is a common disease in males and at early ages of life, and there is no diﬀerence between the populations of the coast, highlands and jungle of Peru, with the overall objective of this research to assess how the unripe papaya juice can treat gastric Ulcer in UPH students and speciﬁc objectives determine the percentage of students who suffer from gastric ulcer, which are the main symptoms and major secondary metabolites containing the unripe papaya juice, held at the medical ofﬁce and research laboratory at 301 UPH racing incoming students of Pharmaceutical Sciences and Biochemistry, Nursing and midwifery, including a description of clinical cases collected as a result ﬁnding that 25% of gastric ulcer symptoms, with the Frequently the acid regurgitation into the mouth (16%), located on the epigastrium pain (15%) and heartburn (13% and the main secondary metabolites were terpenoids, alkaloids, ﬂavonoids, carbohydrates, saponins and steroidal substances in magnitude + + +.